To be or not to be: problems in locating women in public policy - Jain, Devaki (2007)
This paper discusses some of the problems women face in gendering public policy. The paper elaborates on how women's collective identity can be forceful politically when backed by knowledge and gives examples of this from Karnataka. New developments in decentralisation of governance have opened possibilities for women's agency at the local level. Paradoxically, developments at the global level have the possibility of undermining this process. The author argues that we can only therefore confront this not be integrating into the existing development paradigm and attempting small changes at the local level but by evolving a different development paradigm that will ensure justice for the majority of the poor and women. - Reproduced.
Keywords: Public policy; Women